Disaster research: a nursing opportunity. Issue 3 (31st July 2013) - Giarratano, Gloria; Savage, Jane; Barcelona‐deMendoza, Veronica; Harville, Emily W.
<x xml:space="preserve">Abstract</x> Nurses working or living near a community disaster have the opportunity to study health‐related consequences to disaster or disaster recovery. In such a situation, the researchers need to deal with the conceptual and methodological issues unique to postdisaster research and know what resources are available to guide them, even if they have no specialized training or previous experience in disaster research. The purpose of this article is to review issues and challenges associated with conducting postdisaster research and encourage nurses to seek resources and seize opportunities to conduct research should the situation arise. Current disaster studies and the authors' personal experiences conducting maternal‐child research in post‐Katrina New Orleans (2005–2013) provide real‐life examples of how health professionals and nurses faced the challenges of doing postdisaster research. After catastrophic events, nurses need to step forward to conduct disaster research that informs and improves future disaster planning and healthcare responses.